Religiusitas dan perilaku prososial santri - Susilo, Hendra Budi; Permadi, Dimas Agil; Ubaidillah, Fauzul Adim; Hasan, Nur (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
Santri are people who undergo Islamic religious education at Islamic boarding schools and it is hoped that they will be able to apply religious teachings in their daily lives. Prosocial behavior is one of the most important things in achieving Rahmatan Lil'alamin behavior. This research aims to find out the relationship between religiosity and resilience. This research used quantitative methods by collecting a sample of 94 from 117 male students at the Salafiyah Safi'iyah Sukorejo Islamic Boarding School who came from NTB. This research uses 2 scales, namely religiosity and prosocial behavior. The religiosity scale is based on aspects of Huber and Huber (2012) and the prosocial scale is based on aspects of Eisenberg & Mussen (1989). The data obtained were analyzed using Spearman Rho correlation because it did not meet the normality assumption. The research results show that religiosity has a positive and significant relationship with prosocial behavior, meaning that the higher the religiosity, the higher the prosocial behavior.